The family in comparative paremies of Tuvan, Swedish and Russian languages - Zinovieva, Elena I.; Alyoshin, Alexey S. (The New Research of Tuva, 2022)
The article deals with proverbs and sayings of a comparative structure about family members and kinfolk in Tuvan, Swedish and Russian. Comparison is a universal method of cognition; however, in every linguistic culture nationally-marked images of comparison do exist. They are conditioned by history, economic life, and the system of values. The structure of the paremias that verbalize the ideas of traditional culture in each of the three considered languages is also different. For sources of our study, we have chosen B.K. Budup’s collection “Proverbs and sayings of the Tuvan people” (2020), V.I. Dahl’s “Proverbs of the Russian people” (1984), and Swedish paremiological dictionaries by P. Holm (1984) and F. Strom (1929). The article examines the typical models of proverbs, reflecting the way of thinking of native speakers of each of the languages, the roles of the subject and object of comparison, words referring to the objects of life, zoonyms and other images of comparison. For Tuvan language, typical are paremies of a four-part structure, which mainly reflect the distribution of maternal and paternal functions in the family. Comparison and imitation of family members is carried out through words referring to animals common for Tuvan culture – the horse, the camel; tools and attributes of economic life – the knife, the flint, the needle. In Swedish language, proverbs typically feature several subjects aligned together, while comparison through opposition is more characteristic of the paremias of the Russian language. Swedish comparative paremias sound more categorical due to the prevailing explicit comparison. Tuvan paremias, in contrast to Russian ones, mainly characterize kinfolk (blood relatives). The general cognithemes concerning the value of children in the family and the role of parents coincide in the paremies of all the three languages. Among private, ethnospecific cognithemes are “the special bond between father and son” in Tuvan paremies, “a daughter is someone else’s treasure” in Russian paremiological units, and “raising children in strictness so that parents do not have to be ashamed in the future” in Swedish ones.